PEMANFAATAN MESIN PEMILAH IJUK UNTUK MENINGKATKAN PRODUKTIVITAS PEMBUAT SAPU IJUK - Kuntang21; Wawan Trisnadi Putra; Fauzan Masykur; Beni Yulio Eka Pratama (JURNAL ABDIMAS DOSMA (JAD), 2023)
The sorting of fibers carried out by home industry players is still traditional, which is still sorting manually by hand. Seeing this situation the author tries to make a tool that makes it easier for the work whose activities are to sort the fibers so that it can be finished quickly with satisfactory results. Work capacity will be prioritized in the work of this machine with the driving energy of the electric motor. The gripping tool or can be referred to as a substitute for the hand in holding the ijut, the chuck will be equipped with a threaded bolt that is useful as a lock so that the fibers cannot move at the time of selection or commonly referred to as sweeping. Based on the data that has been taken, this fiber sorting machine can sort 64 bunches weighing 50 grams and 30 cm in 5 minutes. Using this machine, work safety is guaranteed. In addition, the advantage of using this machine is that the power used is not too much.